2014
DOI: 10.1016/s0924-9338(14)78418-4
|View full text |Cite
|
Sign up to set email alerts
|

EPA-1157 – The influence of medical student gender and drug use on the detection of addiction in patients

Abstract: Introduction:Little is known about medical students’ interest in their training on drug addiction, their personal experience of consumption and whether these aspects influence the detection of addiction in patients.Objectives:To study the interest of medical students enrolled on the psychiatry course in the area of addictions, and evaluate the influence of such interest, a history of personal consumption and gender on the detection of addiction in patients.Aims&Methods:Voluntary participation was offered to al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
1
5
1
4
Order By: Relevance
“…Esta cifra es muy superior a la observada en datos de población general española, en la que los datos para la franja de edad de 15 a 24 años, obtenidos mediante el cuestionario AUDIT, con punto de corte "estándar" (8 para ambos sexos), reflejan un CRA del 7,2% (Ministerio de Sanidad, 2017). La revisión realizada por Roncero et al (2015) apunta a una prevalencia mundial de CRA en estudiantes de medicina del 24%, de acuerdo a las puntuaciones obtenidas en el cuestionario CAGE (punto de corte 2 para ambos sexos) y/o en el AUDIT (punto de corte "estándar") y/o al consumo semanal referido de al menos 21 o 14 unidades de bebida estándar en varones o mujeres, respectivamente.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Esta cifra es muy superior a la observada en datos de población general española, en la que los datos para la franja de edad de 15 a 24 años, obtenidos mediante el cuestionario AUDIT, con punto de corte "estándar" (8 para ambos sexos), reflejan un CRA del 7,2% (Ministerio de Sanidad, 2017). La revisión realizada por Roncero et al (2015) apunta a una prevalencia mundial de CRA en estudiantes de medicina del 24%, de acuerdo a las puntuaciones obtenidas en el cuestionario CAGE (punto de corte 2 para ambos sexos) y/o en el AUDIT (punto de corte "estándar") y/o al consumo semanal referido de al menos 21 o 14 unidades de bebida estándar en varones o mujeres, respectivamente.…”
Section: Discussionunclassified
“…Los varones de esta muestra presentaron una puntuación mayor que las mujeres para las tres preguntas del cuestionario, lo que significa que beben con mayor frecuencia, mayor cantidad y mayor intensidad que los estudiantes de medicina de sexo femenino. Esto va en consonancia con los datos disponibles en población general española (Ministerio de Sanidad, 2017), y en estudiantes de medicina (Lamberti et al, 2017;Roncero et al, 2015) y universitarios de otras nacionalidades (Kolšek & Klemenc Ketiš, 2015).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Phillips et al proposed intensive education of medical students about the importance of healthy eating habits and lifestyle medicine, which aims to prevent, treat, or modify noncommunicable chronic diseases by helping people to make sustainable lifestyle changes (30). Many studies have investigated the prevalence of regular illicit drug use among students (31)(32)(33). One in particular, a systematic review of the literature carried out by Roncero et al, found that students in the later years of medical school have a higher rate of substance abuse than younger students in the earlier years (33).…”
Section: Discussionmentioning
confidence: 99%